BCR-ABL-negative myeloproliferative Neoplasien - Metzgeroth, Georgia; Lengfelder, Eva; Griesshammer, Martin; Reiter, Andreas (Der Onkologe, 2012)
BCR-ABL negative myeloproliferative neoplasms are a heterogeneous group of disorders characterized by a proliferation of one or more myeloid cell lineages. The most common entities are polycythemia vera, essential thrombocythemia and myelofibrosis in which Janus kinase (JAK) and myeloproliferative leukemia virus oncogene (MPL) mutations are found in 60-70% of patients resulting in constitutive activation of the JAK-STAT signal transduction pathway. The clinical and morphological characteristics in peripheral blood and bone marrow are nowadays regularly complemented by cytogenetic and molecular analyses. Precise diagnostic criteria and prognostic markers allow a reliable evaluation of the therapeutic options. Effective targeted therapies have now been developed against pathogenetic signaling pathways, e.g. JAK inhibitors, which in the future will possibly be used as monotherapy or in combination with or without subsequent allogeneic stem cell transplantation.
Gesehen am 28.11.2018